2020
DOI: 10.1002/mus.27077
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of smooth muscle dysfunction among children with Duchenne muscular dystrophy

Abstract: Smooth muscle dysfunction in Duchenne muscular dystrophy (DMD) has been rarely studied. A cross-sectional study was conducted to estimate the prevalence of smooth muscle dysfunction (vascular, upper gastrointestinal, and bladder smooth muscle) in children with DMD using questionnaires (Pediatric Bleeding Questionnaire, Pediatric Gastroesophageal Symptom Questionnaire, and Dysfunctional Voiding Symptom Score). Investigations included bleeding time estimation, nuclear scintigraphy for gastroesophageal reflux, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Gastro–oesophageal reflux requiring treatment was rarely reported but almost half the study group complained of constipation. In a study of the prevalence of smooth muscle dysfunction in children with DMD, Manokaran et al (2020) found that 21% had gastro-oesophageal reflux [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gastro–oesophageal reflux requiring treatment was rarely reported but almost half the study group complained of constipation. In a study of the prevalence of smooth muscle dysfunction in children with DMD, Manokaran et al (2020) found that 21% had gastro-oesophageal reflux [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The DMD pig model of muscular dystrophy also exhibits abnormal digestion and absorption capacity in the gastrointestinal tract [384]. The associated patterns of malnutrition are in agreement with gastrointestinal dysfunction in the dystrophic phenotype [26,177,186,200].…”
Section: Impaired Energy Metabolism Abnormal Liver Function and Gastrointestinal Abnormalities In Dystrophinopathymentioning
confidence: 90%
“…In the second decade of life, cardiomyopathy and respiratory failure requires ventilatory assistance and intervention with cardiac drug treatment [ 161 , 216 ]. Duchenne patients also exhibit an increased susceptibility for fatty liver disease, gastrointestinal complications, renal failure, and bladder dysfunction [ 26 , 200 , 357 ]. Steady advances in cardiopulmonary care and pharmacological therapy have preserved quality of life and improved prognosis for survival of Duchenne patients in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides chronic skeletal muscle wasting [ 23 , 24 ] and impaired neuromuscular transmission [ 293 ], Duchenne patients suffer from multi-system dysfunction [ 29 , 30 , 31 ] involving a variety of tissue and organ systems [ 32 , 33 , 34 ]. These body-wide abnormalities include cardiomyopathy [ 294 , 295 , 296 ], respiratory failure [ 297 , 298 , 299 , 300 ], liver atrophy [ 301 , 302 ], renal failure [ 303 , 304 , 305 , 306 ], bladder dysfunction [ 307 , 308 , 309 , 310 ] and gastrointestinal complications [ 311 , 312 , 313 ], as well as bone fragility [ 314 ] and scoliosis [ 315 , 316 , 317 ]. A subset of Duchenne patients suffers from neurological deficiencies that manifest themselves as neurodevelopmental delays, emotional disturbances, mental retardation and behavioral problems [ 318 , 319 , 320 , 321 , 322 ].…”
Section: The Pathoproteomic Profiling Of Duchenne Muscular Dystrophymentioning
confidence: 99%